Condorcet meets Ellsberg. Issue 3 (September 2016) - Ellis, Andrew
Abstract : The Condorcet Jury Theorem states that given subjective expected utility maximization and common values, the equilibrium probability that the correct candidate wins goes to 1 as the size of the electorate goes to infinity. This paper studies strategic voting when voters have pure common values but may be ambiguity averse—exhibit Ellsberg‐type behavior—as modeled by maxmin expected utility preferences. It provides sufficient conditions so that the equilibrium probability of the correct candidate winning the election is bounded above by 1⁄2 in at least one state. As a consequence, there is no equilibrium in which information aggregates.